2007
DOI: 10.1182/blood-2006-10-051276
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of integrins α6 and α4 in homing of fetal liver hematopoietic stem and progenitor cells

Abstract: Homing of hematopoietic stem cells (HSCs) into the bone marrow (BM) is a prerequisite for establishment of hematopoiesis during development and following transplantation. However, the molecular interactions that control homing of HSCs, in particular, of fetal HSCs, are not well understood. Herein, we studied the role of the ␣6 and ␣4 integrin receptors for homing and engraftment of fetal liver (FL) HSCs and hematopoietic progenitor cells (HPCs) to adult BM by using integrin IntroductionDuring transplantation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 71 publications
1
47
0
1
Order By: Relevance
“…28,29 Our current study demonstrates that another member of the integrin β1-subfamily, the integrin α9β1, is also very important for HSPC biology. The integrin α9β1 can be detected on almost all early CD133 + HSPC.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Our current study demonstrates that another member of the integrin β1-subfamily, the integrin α9β1, is also very important for HSPC biology. The integrin α9β1 can be detected on almost all early CD133 + HSPC.…”
Section: Discussionmentioning
confidence: 99%
“…HSC Homing to the BM and Spleen-HSC homing assays were essentially performed as described previously (28,29). Briefly, transduced KSL cells (1 ϫ 10 5 cells) were injected into lethally irradiated recipient mice (9.5 grays).…”
Section: Isolation Of C-kitmentioning
confidence: 99%
“…In contrast, similar experiments with fetal liver cells revealed that, in contrast to CD49d which appeared to be important for homing of both hematopoietic stem and progenitor cells, CD49f is only important for homing of hematopoietic progenitors but not stem cells (Qian et al, 2007). These studies indicate that CD49d and Cd49f play differential roles during homing of cord blood and fetal liver derived hematopoietic stem and progenitor cells (Qian et al, 2007). In contrast, bone marrow homing was not affected in a more recent study in which also mouse bone marrow derived hematopoietic stem and progenitor cells pretreated with blocking antibodies directed against CD49f were transplanted in recipient mice (Bonig et al, 2009).…”
Section: Integrins and Bone Marrow Homingmentioning
confidence: 81%
“…In contrast to CD49d that appears to primarily be involved in bone marrow homing of short-term repopulating hematopoietic stem cells, CD49f is thought to be important for homing of both short-term and long-term stem cells (Qian et al, 2006). In contrast, similar experiments with fetal liver cells revealed that, in contrast to CD49d which appeared to be important for homing of both hematopoietic stem and progenitor cells, CD49f is only important for homing of hematopoietic progenitors but not stem cells (Qian et al, 2007). These studies indicate that CD49d and Cd49f play differential roles during homing of cord blood and fetal liver derived hematopoietic stem and progenitor cells (Qian et al, 2007).…”
Section: Integrins and Bone Marrow Homingmentioning
confidence: 90%